Implementation of Inclusive Education in Indonesian Regular School: A Literature Review - Tri Wahyuni; Sowiyah; Hasan Hariri (Social Science Studies, 2021)
This review aimed to determine the implementation of inclusive education in regular schools. The implementation of education in regular schools has many obstacles, including teachers’ lack of the ability to manage inclusive schools. Teachers in this case are an important part of schools to run programs smoothly because teachers communicate directly with students in need. Students, knowledge, skills and experience of teachers determine how well inclusive programs are run in schools, especially in the classroom. To achieve that, teachers need to have several trainings to help them prepare and carry out their plans properly. An e-literature search was conducted to identify articles published from 2015 to 2021 on the steps needed to optimize teacher skills to achieve a good inclusive environment. The electronic database used is Google Scholar. This study used review. Based on the articles reviewed, it was found that the implementation of inclusive education in regular schools was done by improving the skills of teachers through co-teaching training. Apart from teachers, schools and parents were provided with sufficient information about inclusive programs and how to do them. The seven articles' findings were reviewed by the researchers, and indicate that several things must be done in the implementation of inclusive education in public schools. The teacher is the main concern in inclusive learning because the teacher is a school device that interacts directly with students and at the same time provides teaching to students in the classroom.